Aproveitamento de água pluvial em edifícios residenciais multifamiliares na cidade de São Carlos - Campos, Marcus André Siqueira (2004)
The potable water scarcity afflicts the begging of the 21st Century, being today, one of the main worries of the manhood. This way, it becomes necessary to reduce the per capita consumption. From the actions that promote the racional use of water, the technological ones seems to be , in the most of the cases, the most recomended to reduce the consumption without being necessary radical changes of the users. One of these technologies is the rainwater harvesting. This one erges as an action of good perspectives since it subistitutes the use of potable water in activities where it is not necessary a good quality water, younder, it will reduce the amount of stormwater in the public drainage net, working as a non-structural action of urban drainage. The lack of kwondlege as well a the real advantages that a rainwater system can bring to a builind, is the points to find out about this issue.. At this paper, it seeked to clear this techonolgy up with the study of national and international examples . It also seeked the cistern sizing, getting the best results to technical and economical issues, as well, as procedures to design and to mantain the devices that make part of the system used in this study. Besides that, it studied the changes that would be necessary to build the system, and the possibles changes at the work routine of the construction company. It also studied the financial feasibility of the investiment of this interprisement, checking the real economical advantages that can be get. It is waited that this research contributes to the development of this techonology, contributing to Racional use of water in residential tall buildings.